THE EFFECT OF COMPETENCE, DISCIPLINE AND MOTIVATION TO PERFORMANCE FUNCTIONAL OFFICIALS IN THE MINISTRY OF ENVIRONMENT AND FORESTRY IN SOUTH SUMATRA PROVINCE - Muhammad Idris, Choiriyah , Afan Absori (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Performance is affected by a few variables counting competence, motivation and discipline. The reason of this think about was to look at the impact of competence, discipline and motivation on the performance of functional officials at the Ministry of Environment and Forestry in South Sumatra Province . The nature of this study is correlational using a sample of 104 respondents. Using three independent variables and one dependent variable, data collection techniques were carried out using questionnaires and interviews and direct observation in the field. As a research instrument used validity test, reliability test, data normality test, heteroscedasticity test, and multicollinearity test. The analytical method uses the determinant coefficient test, the F test, and the t test. The results of the research R square value of 0.466 means that the independent variable (X) influences the dependent variable (Y) of 46.6%. Fcount value 29.045> Ftable 2.69 and sig value 0.000 <0.05, so that competency, discipline and motivation together have a significant effect on the performance of functional officials at the Ministry of Environment and Forestry in South Sumatra Province. Partially, competence has a significant effect on the performance of the value of t 2.563> t table 1.987 and sig 0.012 <0.05. Discipline has a significant effect on the performance of tcount 2.576> t table 1.987 and sig 0.011 <0.05. Motivation did not have a significant effect on the performance of the tcount of 1.946 0.05. In the practical aspects of this study as input for functional officials and employee coaching material for performance improvement academically become a reference for further research.